Analysis of the consent of the non-abducting parent to the removal or retention of the child. Interpretation of the Spanish Court of Appeal of Barcelona (Ceccion 18ª) of 27th NovemberJune - Herranz Ballesteros, Mónica (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
International Child Abduction from Corea to Spain. Application of article 13 a) of the Hague Convenion on Civil Aspects of International Child Abduction of 1980. Father’s permission. Non wrongful retention.